Analyzing the Influence of Japanese Language Proficiency and Internship Experience on Students’ Readiness for Professional Engagement - Renold; Taqdir; Alghifari, Muhammad Faiz; Gosal, Squal William; Muhammad Salim, Muhammad Arfin (Eduvelop: Journal of English Education and Development, 2025)
This study explores the influence of Japanese language proficiency and internship experience on students’ readiness for professional engagement within Japanese-speaking tourism service environments. Focusing on students from the Diploma 4 Tourism Business Program and the Diploma 3 Travel Program at Makassar Tourism Polytechnic, the research addresses the persistent gap between academic language instruction and real-world communicative competence in Japanese Language Skills contexts. A quantitative method was employed, involving 124 students who had completed internships and enrolled in elective Japanese language courses. Data were analyzed using SmartPLS version 4.1.1.4, incorporating outer and inner model assessments such as convergent validity, discriminant validity, composite reliability, R², f², and hypothesis testing for both direct and indirect effects. The findings indicate that internship experience has a significantly strong influence on students’ readiness to interact with Japanese partners (f² = 0.8398; p < 0.001), while general Japanese language proficiency exerts a moderate yet meaningful impact. Conversely, basic text mastery and formal Japanese communication skills show weak and statistically insignificant effects. These results underscore the vital role of experiential learning in enhancing functional language application in professional settings. The study recommends integrating practical language activities into internships and strengthening collaboration between academic programs and industry. Future research should examine the quality of internship placements and evaluate ESP outcomes across different hospitality and tourism programs